IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DALAM MATA KULIAH STATISTIK DASAR PADA PROGRAM STUDI PENDIDIKAN BIOLOGI - Yani, Ahmad; Ningsih, Kurnia (Universitas Tanjungpura, 2018)
This aims this study is to obtain objective information about the learning outcome after implementation of type STAD cooperative learning model on basic statistics course in third semester of PAPK Program in Biology Education. In addition, this study develop students?s ability to understand in working together to solve and resolve the problem. The samples of study were third semester students in PAPK program who follow the Basic Statistics course in Biology Education Departement of PMIPA FKIP Untan 2016-2017. Implementation in the data presentation focused on the subject matter, size and placement of the central symptoms.The data collection conducted in providing achievement test after being given treatment. Form of test is essay with 2 questions which consist of 13 questions. The results showed if the type STAD cooperative learning model is one model that could improve student?s outcome on the subject presentation of the data, the size of the placement and symptoms in statistics basic course.Keyword: STAD cooperative learning model